Microcirculatory Response to Changes in Venoarterial Extracorporeal Membrane Oxygenation Pump Flow: A Prospective Observational Study - Wei, Tzu-Jung; Wang, Chih-Hsien; Chan, Wing-Sum; Huang, Chi-Hsiang; Lai, Chien-Heng; Wang, Ming-Jiuh; Chen, Yih-Sharng; Ince, Can; Lin, Tzu-Yu; Yeh, Yu-Chang (Frontiers in Medicine, 2021)
Background. Venoarterial extracorporeal membrane oxygenation (VA-ECMO) pump flow is crucial for maintaining organ perfusion in patients with cardiogenic shock, but VA-ECMO pump flow optimization remains as a clinical challenge. This study aimed to investigate the response of sublingual microcirculation to changes in VA-ECMO pump flow. Methods. Sublingual microcirculation was measured before and after changing VA-ECMO pump flow according to the treatment plan of ECMO team within 24 h and at 24-48 h after VA-ECMO placement. In clinical events of increasing VA-ECMO pump flow, those events with increased perfused vessel density (PVD) were grouped into group A, and the others were grouped into group B. In clinical events of decreasing VA-ECMO pump flow, those events with increased PVD were grouped into group C, and the others were grouped into group D. Results. Increased PVD was observed in 60% (95% CI, 38.5%−81.5%) of the events with increasing VA-ECMO pump flow. The probability of increasing PVD after increasing VA-ECMO pump flow were higher in the events with a PVD < 15 mm/mm2 at baseline than those with a PVD ≥ 15 mm/mm2 (100% [95% CI, 54.1%−100%] vs 42.9% [95% CI, 17.7%−71.1%], P = 0.042). Other microcirculatory and hemodynamic parameters at baseline did not differ significantly between group A and B or between group C and D. Conclusion. This study revealed contradictory and noncontradictory responses of sublingual microcirculation to changes in VA-ECMO pump flow. Tandem measurements of microcirculation before and after changing VA-ECMO pump flow may help to ensure a good microcirculation.